2020
DOI: 10.1007/s10683-020-09645-z
|View full text |Cite
|
Sign up to set email alerts
|

Altruism, fast and slow? Evidence from a meta-analysis and a new experiment

Abstract: Can we use the lens of dual-system theories to explain altruistic behavior? In recent years this question has attracted the interest of both economists and psychologists. We contribute to this emerging literature by reporting the results of a meta-study of the literature and a new experiment. Our meta-study is based on 22 experimental studies conducted with more than 12,000 subjects. We show that the overall effect of manipulating cognitive resources to promote the "intuitive" system at the expense of the "del… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

12
58
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(73 citation statements)
references
References 62 publications
12
58
3
Order By: Relevance
“…However, a more recent meta-analysis (Fromell, Nosenzo & Owens, 2018) found an interaction between gender and cognitive mode, in a slightly different direction than Rand et al (2016). Specifically, Fromell et al (2018) meta-analysed 19 studies (total N = 10,898) and, in line with Rand et al (2016), they found that there is an interaction between gender and cognitive process manipulation; however, in contrast to Rand et al (2016), they found that promoting System 1 has no effect on women, whereas it has a marginally significant negative effect on men. It is worth noticing that Fromell et al (2018) used broader inclusion criteria than those used by Rand et al (2016).…”
Section: Meta-analyses and The Mysterious Role Of Gendermentioning
confidence: 77%
See 4 more Smart Citations
“…However, a more recent meta-analysis (Fromell, Nosenzo & Owens, 2018) found an interaction between gender and cognitive mode, in a slightly different direction than Rand et al (2016). Specifically, Fromell et al (2018) meta-analysed 19 studies (total N = 10,898) and, in line with Rand et al (2016), they found that there is an interaction between gender and cognitive process manipulation; however, in contrast to Rand et al (2016), they found that promoting System 1 has no effect on women, whereas it has a marginally significant negative effect on men. It is worth noticing that Fromell et al (2018) used broader inclusion criteria than those used by Rand et al (2016).…”
Section: Meta-analyses and The Mysterious Role Of Gendermentioning
confidence: 77%
“…Specifically, Fromell et al (2018) meta-analysed 19 studies (total N = 10,898) and, in line with Rand et al (2016), they found that there is an interaction between gender and cognitive process manipulation; however, in contrast to Rand et al (2016), they found that promoting System 1 has no effect on women, whereas it has a marginally significant negative effect on men. It is worth noticing that Fromell et al (2018) used broader inclusion criteria than those used by Rand et al (2016). In particular, they included also dictator games in which the recipient was a charitable organization and those with varying cost-to-benefit ratio.…”
Section: Meta-analyses and The Mysterious Role Of Gendermentioning
confidence: 89%
See 3 more Smart Citations